Optimizing Service Scheduling by Genetic Algorithm Support Decision-Making in Smart Tourism Destinations - Pannee Suanpang; Pitchaya Jamjuntr (Decision Making: Applications in Management and Engineering, 2024)
Smart tourism destinations are characterised by the integration of advanced technologies and devices to ensure visitors enjoy a seamless and environmentally responsible experience. A key challenge for such destinations lies in efficiently managing and delivering services to meet tourists' expectations while upholding sustainability principles and resource management practices. This study aimed to explore the application of genetic algorithms (GAs) in optimising service scheduling, thereby supporting decision-making processes and enhancing tourism destination services. The research employed a service scheduling methodology that directed the algorithm towards maximising efficiency and customer satisfaction, in contrast to traditional organisational scheduling methods. The methodology centred on the implementation of an algorithmic approach in service delivery management, prioritising operational efficiency and improved customer experience over conventional scheduling techniques. Data collected were systematically analysed, resulting in the development of a theoretical framework based on the findings. The results demonstrated that genetic algorithms significantly enhance service scheduling efficiency when used alongside other methods. The findings underscore the pivotal role of GAs in enabling businesses to achieve time and cost savings while improving customer satisfaction. Furthermore, the study highlights GAs' capacity for adaptability, allowing schedules to be adjusted rapidly in response to changing circumstances, thus providing flexibility and responsiveness to variations in demand. Finally, the research identifies opportunities for innovation and diversification in applying GAs for time scheduling within the tourism sector. It also emphasises the importance of integrating real-time information into scheduling systems to improve service provision at tourist sites. This approach not only enhances the competitiveness of tourism destinations but also adds substantial value to the industry by enriching tourists' experiences and fostering sustainable practices